Effect of split sleeve cold expansion on microstructure and fatigue performance of 7075-T6 aluminum alloy holes. (February 2023) - Wang, Chenguang; Zou, Fan; Zhou, Entao; Fan, Zhilei; Ge, Ende; An, Qinglong; Ming, Weiwei; Chen, Ming
Highlights: After SCE treatment, evident residual stress and improved hardness can be observed on the surface of aluminum alloy holes. SCE process has more obvious effect on high cycle fatigue life of 7075-T6 aluminum alloy holes. The SCE process leads to obvious plastic deformation on the surface of the holes, grain refinement, and an increase in the proportion of LABs. The formation mechanism of gradient nanograins on the surface of the aluminum alloy holes after SCE treatment was revealed. The gain effect of the SCE process on the fatigue initiation stage of the holes is more prominent. Abstract: 7075-T6 aluminum alloy is widely used in the manufacture of various structural parts of aircraft, most of which are joined and assembled through hole structures. However, stress concentration will occur around the hole during the service process of the part, which is easy to cause fatigue failure. It is significant to improve the fatigue performance of the hole structure. In this work, surface strengthening of 7075-T6 aluminum alloy holes induced by split sleeve cold expansion (SCE) was studied regarding surface microstructure, microhardness, and residual stress profiles. The effects of SCE process on the fatigue properties in different stress levels were finally discussed. The results show that the surface of the SCE sample undergoes severe plastic deformation and forms a gradient grain structure with a layer of nanocrystals in the outermost layer. This process lead to an increase of surface microhardness by about 14.3% and a compressive residual stress of up to 255 MPa. Dislocation slip is dominant deformation mechanism in the expansion process. During expansion, more dislocation tangles, dislocation walls and dislocation cells appear, which induces the formation of sub-grain boundaries and refines the grains. In the SCE samples, the high-strength nanocrystals on the surface of holes, the excellent resistance to strain localization of the gradient structure and the high compressive residual stress can effectively hinder the initiation of fatigue cracks and increase the high-cycle fatigue life by 9 times.